Amino acids in the polymerase complex of shorebird-isolated H1N1 influenza virus impact replication and host-virus interactions in mammalian models - Bai, Yaqin; Lei, Hui; Song, Wenjun; Shin, Sang Chul; Wang, Jiaqi; Xiao, Biying; Ko？er, Zeynep A.; Song, Min-Suk; Webster, Robert; Webby, Richard; Wong, Sook-San; Zanin, Mark (Nature Publishing Group, 2024)
A diverse population of avian influenza A viruses (AIVs) are maintained in wild birds and ducks yet the zoonotic potential of AIVs in these environmental reservoirs and the host-virus interactions involved in mammalian infection are not well understood. In studies of a group of subtype H1N1 AIVs isolated from migratory wild birds during surveillance in North America, we previously identified eight amino acids in the polymerase genes PB2 and PB1 that were important for the transmissibility of these AIVs in a ferret model of human influenza virus transmission. In this current study we found that PB2 containing amino acids associated with transmissibility at 67, 152, 199, 508, and 649 and PB1 at 298, 642, and 667 were associated with more rapid viral replication kinetics, greater infectivity, more active polymerase complexes and greater kinetics of viral genome replication and transcription. Pathogenicity in the mouse model was also impacted, evident as greater weight loss and lung pathology associated with greater inflammatory lung cytokine expression. Further, these AIVs all contained the avian-type amino acids of PB2-E627, D701, G590, Q591 and T271. Therefore, our study provides novel insights into the role of the AIV polymerase complex in the zoonotic transmission of AIVs in mammals.